Field evaluation and determination of four herbicides in a wheat ecosystem by a simple and versatile QuEChERS method with liquid chromatography-tandem mass spectrometry. Issue 3 (16th March 2017) - Pang, Nannan; Wang, Tielong; Hu, Jiye; Dong, Bizhang
ABSTRACT: Wheat products are consumed worldwide and every day; therefore, herbicides misuse in the wheat ecosystem has become a global food safety issue. Here, a simple and versatile method, QuEChERS (quick, easy, cheap, effective, rugged, and safe) with liquid chromatography-tandem mass spectrometry was developed to measure four herbicides in soil, wheat, and wheat straw – florasulam, carfentrazone-ethyl, fluroxypyr-meptyl, and fluroxypyr. By adjusting the amount of graphitized carbon black from 0 to 10 mg, the herbicides could be extracted with satisfactory recoveries of 80%–110%. Application of two water-dispersible granules showed first-order kinetics as well as half-lives between 1.2 and 5.1 d under open-field conditions. The dissipation kinetics of the four herbicides differed in the soil, wheat, and wheat straw, with residual concentrations in straw at 2 h after application being higher than in soil and faster degradation occurring in straw. The terminal residues in soil, wheat grain, and wheat straw were all below the maximum residue limits. The developed method was easy to handle and versatile; thus, it will facilitate regulation and inspection for possible misuse against Good Agriculture Practices. Moreover, the results of this study will contribute to global environmental protection as well as food safety issues.